1998
DOI: 10.1111/j.1600-0528.1998.tb01961.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a dental benefit plan for children conducted in Auvergne, France, since 1992

Abstract: Usually, the French dental insurance system covers the cost of restorative treatment but does not reimburse the cost of preventive therapies. A French sick-fund covering self-employed persons tested a new dental benefit plan for children intended to provide an incentive to develop office-based preventive activities. The programme, which started in 1992, concerns all 4-year-old children of self-employed workers in a single French region (Auvergne). Participants undergo an annual examination by the dentist of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
1
4
0
2
Order By: Relevance
“…Taking into account the prevalence of fissure sealants, the DMFT values of the different subgroups, and indications regarding dental attendance frequencies, it is concluded that practitioners in Heidelberg focus more on primary prevention, whereas the independent dentists in Montpellier perform more secondary preventive measures. This assumption accords with the findings of Tubert-Jeannin et al (21) who pointed out that French dentists would prefer to undertake restorative procedures as opposed to practicing preventive measures. Furthermore, the responses of children in Montpellier revealed that they saw a dentist only when they or their parents had observed a pathologic change in at least one tooth.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Taking into account the prevalence of fissure sealants, the DMFT values of the different subgroups, and indications regarding dental attendance frequencies, it is concluded that practitioners in Heidelberg focus more on primary prevention, whereas the independent dentists in Montpellier perform more secondary preventive measures. This assumption accords with the findings of Tubert-Jeannin et al (21) who pointed out that French dentists would prefer to undertake restorative procedures as opposed to practicing preventive measures. Furthermore, the responses of children in Montpellier revealed that they saw a dentist only when they or their parents had observed a pathologic change in at least one tooth.…”
Section: Discussionsupporting
confidence: 86%
“…On the one hand, this may indicate that dentists in Montpellier apply fissure sealants in children with a higher caries risk, as is indicated by the fillings and carious lesions present in these children. On the other hand, the importance of the fact that fissure sealants are not paid for by the social security service must not be underestimated (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Restorative treatments are listed, but professionally provided preventive care (except sealants) does not generally qualify for reimbursement, which consequently discourages prevention and encourages operative care. 9,36 This system of remuneration does not promote comprehensive care, as treatments conserving and optimizing the longevity of the patient's dentition are not covered. 31 The development of modern concepts in caries management thus depends on other developments to many factors, such as initial and continuous dental education, health education for patients, and the dental care system.…”
Section: Discussionmentioning
confidence: 99%
“…Professionally provided preventive care does not generally qualify for reimbursement, a limi-tation that discourages prevention and encourages operative care. 33 This may influence the curriculum and dental school treatment plans.…”
Section: Discussionmentioning
confidence: 99%